1997
DOI: 10.1093/geront/37.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activity and Satisfaction Among Very Old Adults: Results From a Community-Dwelling Medicare Population Survey

Abstract: This article explores the relationship between sociopsychological factors, sexual activity, and sexual satisfaction in a sample of 1,216 elderly people (mean age = 77.3). Almost 30% had participated in sexual activity in the past month and 67% were satisfied with current level of sexual activity. Men are more likely to be sexually active, but less apt than women to be satisfied with their level of sexual activity. Regarding predictors of sexual activity, for men the strongest predictors were being younger and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
74
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(87 citation statements)
references
References 21 publications
7
74
1
5
Order By: Relevance
“…The vast majority of work has also been undertaken within the US and very few UK-specific studies could be identified. For example, from the literature we can identify that older people in the US are sexually active (implicitly equated with sexual intercourse, although generally not defined), and that being male, [7][8][9][10][11][12][13] being in a 'young elderly' age-banding (i.e. 50-70 years), 9,13-16 being married, 8,11,13 being in good physical and mental health, 8,11,17 being well-educated, 13 having a good social network 13 and being sexually active and interested when younger 8,18 can be predictive of later-life sexual activity.…”
Section: Later-life Sexualitymentioning
confidence: 99%
“…The vast majority of work has also been undertaken within the US and very few UK-specific studies could be identified. For example, from the literature we can identify that older people in the US are sexually active (implicitly equated with sexual intercourse, although generally not defined), and that being male, [7][8][9][10][11][12][13] being in a 'young elderly' age-banding (i.e. 50-70 years), 9,13-16 being married, 8,11,13 being in good physical and mental health, 8,11,17 being well-educated, 13 having a good social network 13 and being sexually active and interested when younger 8,18 can be predictive of later-life sexual activity.…”
Section: Later-life Sexualitymentioning
confidence: 99%
“…13,14 Moreover, relatively little is known about the average frequency of sexual activity and the importance of sexual relationships among older men and women, although the few studies that have examined sexuality in mature adults have reported that sexual interest and activity persist well into older age. 15,16 The published studies of the prevalence and correlates of sexual problems in developed and developing countries have used a variety of different study designs and definitions, which makes valid cross-national comparisons difficult. Moreover, there are currently no related studies reporting how men or women from different cultures attempt to manage or overcome their sexual problems, and there are only a few studies that allow a comparison of sexual behaviors across different countries.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Older individuals desire to love and enjoy sexual activity in relation to personal circumstances, and when health status allows them to experience close relations, most often within marriage. [3][4][5] Normal changes occur in the phases of sexual cycle with aging, mainly men needing more time and stimulation to achieve a complete erection. 6 The importance of sex in maintaining a good relationship in a couple persists with advancing age, but is affected by sexual dysfunction (SD).…”
Section: Introductionmentioning
confidence: 99%